RETRACTED: Kiai, Santri, and Nationalism: A Historical Approach to The Jihad Resolution for Indonesian Independence: this article had published in https://ecohumanism.co.uk/joe/ecohumanism/article/view/4076 - Rahman Rahman; Moh. Mujibur Rohman; Ali Akbar; Ahmad Ghozali; Darusman Darusman (TSAQAFAH, 2025)
-